An S‐ to Ku‐wideband low‐noise amplifier using asymmetric π filter and shunt‐peaking technique with simultaneous input match and noise flatness. Issue 6 (10th March 2019) - Jing, Kai; Yu, Ningmei; Quan, Xing
Abstract: A single‐stage S to Ku band (2‐18 GHz) low noise amplifier (LNA) employing asymmetric π input match network and inductive shunt‐peaking technique in 0.18 μm SiGe BiCMOS is presented. Shunt‐shunt feedback is utilized to ensure wide operating as well as form a noise suppression topology. With the process of SiGe heterojunction bipolar transistor (HBT) featuring f T / f max of 240/280 GHz, the measurement of the proposed LNA results in S 11 below −10 dB, S 21 of 19.6 ± 0.8 dB and 2.2‐3.2 dB noise figure (NF) from 2 to 18 GHz, drawing 9 mA DC current from a 3.3 V supply.